2022
DOI: 10.7759/cureus.29905
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis on Bibliometric Studies of Case Reports in the Medical Field

Abstract: The studies on bibliometric analyses of case reports usually give valuable information regarding various aspects of case reports but lack investigation analysing these publications. This is the first-ever study to examine the bibliometric articles on case reports; hence, it is hypothesized to provide a valuable contribution to this gap. PubMed and SCOPUS databases were searched, and a total of 119 articles were obtained, but only five were analyzed matching the inclusion criteria. The keywords involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The field of bibliometrics is closely related with scientometrics, and its objective is to identify the corpus of the literature, as well as its quantitative and statistical analysis. These analyses are necessary for assessing the scientific and clinical activity in a field, as they provide essential information on the current state of progress in specific branches in particular [19][20][21]. Thus, the impact of the scientific literature can be analysed and interpreted for its use in research [19].…”
Section: Introductionmentioning
confidence: 99%
“…The field of bibliometrics is closely related with scientometrics, and its objective is to identify the corpus of the literature, as well as its quantitative and statistical analysis. These analyses are necessary for assessing the scientific and clinical activity in a field, as they provide essential information on the current state of progress in specific branches in particular [19][20][21]. Thus, the impact of the scientific literature can be analysed and interpreted for its use in research [19].…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis is one of the most common approaches applied to scientific research, enabling a quantitative assessment of the literature in different scientific areas, and nanovaccine research is no exception [21][22][23][24]. The use of tools such as Biblioshiny and CiteSpace allows exploration of the field's dynamics, current trends, and prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the field of medicine, they also make some information about unusual symptoms or signs and rare diseases more accessible. Recent research has shown that with the development of interdisciplinary methodologies and increasing technological advances in analysing big data, bibliometric analyses have become more popular and are being performed more frequently than in the past (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%